2012
DOI: 10.3109/17435390.2012.658094
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity, accumulation and transport of silver nanoparticles by Arabidopsis thaliana

Abstract: The widespread availability of nano-enabled products in the global market may lead to the release of a substantial amount of engineered nanoparticles in the environment, which frequently display drastically different physiochemical properties than their bulk counterparts. The purpose of the study was to evaluate the impact of citrate-stabilised silver nanoparticles (AgNPs) on the plant Arabidopsis thaliana at three levels, physiological phytotoxicity, cellular accumulation and subcellular transport of AgNPs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
180
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(198 citation statements)
references
References 74 publications
13
180
3
2
Order By: Relevance
“…Moreover, 111 genes were unique for AgNPs, and they were enriched for three biological functions: response to fungal infection, anion transport, and cell wall/plasma membrane related (Kohan-Baghkheirati and Geisler-Lee, 2015). The expression patterns of genes investigated in this study suggest that they are regulated in response to AgNPs, which represents a novel abiotic stressor for plants (Geisler-Lee et al, 2013;Qian et al, 2013).…”
Section: Figmentioning
confidence: 81%
“…Moreover, 111 genes were unique for AgNPs, and they were enriched for three biological functions: response to fungal infection, anion transport, and cell wall/plasma membrane related (Kohan-Baghkheirati and Geisler-Lee, 2015). The expression patterns of genes investigated in this study suggest that they are regulated in response to AgNPs, which represents a novel abiotic stressor for plants (Geisler-Lee et al, 2013;Qian et al, 2013).…”
Section: Figmentioning
confidence: 81%
“…Our previous study with Arabidopsis also indicated that there is a size limitation on the potential uptake and accumulation of AgNPs. In that study, we found that only AgNPs smaller than 40 nm were successfully internalized in Arabidopsis root cells and some appeared to reach the vascular tissues for possible transport to the shoots (Geisler- Lee et al 2013). Haverkamp and Marshall (2009) also investigated the uptake of Ag ion complexes and AgNPs by Brassica juncea plants.…”
Section: Uptake and Accumulation Of Multi-walled Carbon Nanotubesmentioning
confidence: 99%
“…In general, the toxicity of metal ions significantly exceeds the toxicity of nanoparticles [85], and the phytotoxic effect of Ag NPs is higher than that of Au NPs [86]. The toxic effect was manifested in inhibition of elongation of the arabidopsis roots, an increase in the vegetation period by 2-3 days, a decrease in seed germination rate in the offspring, and, according to the authors, was due to the diffusion of silver ions from the Ag NP surface.…”
mentioning
confidence: 98%